Identifying some determinants of "jet lag" and its symptoms: a study of athletes and other travellers. Issue 1 (1st February 2002) - Waterhouse, J; Edwards, B; Nevill, A; Carvalho, S; Atkinson, G; Buckley, P; Reilly, T; Godfrey, R; Ramsay, R
Abstract : Background: Travelling across multiple time zones disrupts normal circadian rhythms and induces "jet lag". Possible effects of this on training and performance in athletes were concerns before the Sydney Olympic Games. Objective: To identify some determinants of jet lag and its symptoms. Methods: A mixture of athletes, their coaches, and academics attending a conference (n = 85) was studied during their flights from the United Kingdom to Australia (two flights with a one hour stopover in Singapore), and for the first six days in Australia. Subjects differed in age, sex, chronotype, flexibility of sleeping habits, feelings of languor, fitness, time of arrival in Australia, and whether or not they had previous experience of travel to Australia. These variables and whether the body clock adjusted to new local time by phase advance or delay were tested as predictors for jet lag and some of its symptoms by stepwise multiple regression analyses. Results: The amount of sleep in the first flight was significantly greater in those who had left the United Kingdom in the evening than the morning (medians of 5.5 hours and 1.5 hours respectively; p = 0.0002, Mann-Whitney), whereas there was no significant difference on the second flight (2.5 hours v 2.8 hours; p = 0.72). Only the severity of jet lag and assessments of sleep and fatigue were commonly predicted significantly (p<0.05) by regression analysis, and then by only some of the variables. Thus increasing age and a later time of arrival in Australia were associated with less jet lag and fatigue, and previous experience of travel to Australia was associated with an earlier time of getting to sleep. Subjects who had adjusted by phase advance suffered worse jet lag during the 5th and 6th days in Australia. Conclusions: These results indicate the importance of an appropriate choice of itinerary and lifestyle for reducing the negative effects of jet lag in athletes and others who wish to perform optimally in the new time zone.